A Numerical Study of Linear Two-Points Boundary Value Problems with ODEs of Fourth-Order Using RKM Method - Mohammed S. Mechee; F. A. Fawzi; Shaymaa Mahmoud Abdullah (Academic Science Journal)
This study established the numerical RKM approach for solving linear two-point boundary value problems involving fourth-order ordinary differential equations. However, the proposed developed numerical RKM method has been tested using some implementations in order to compare it with the exact solutions to establish the method's validity. Furthermore, this comparison demonstrates that the proposed direct integrator is more efficient than the indirect method in terms of efficiency and accuracy. In addition, numerical implementations are used in order to show the efficiency and time-based complexity of function evaluations. This direct method's suggested strategy, which has wonderful qualities like quick and efficient calculation, also requires fewer computational employees.